A strategy for preparing controllable, superhydrophobic, strongly sticky surfaces using SiO2@PVDF raspberry core–shell particles. Issue 38 (5th July 2021) - Kim, Seung-Hyun; Kang, Hong Suk; Sohn, Eun-Ho; Chang, Bong-Jun; Park, In Jun; Lee, Sang Goo
Abstract : In this study, to control the stickiness of superhydrophobic materials, we propose a new strategy to prepare controllable superhydrophobic structured colloidal coatings with either strong or weak stickiness. Abstract : In nature, wetting by water droplets on superhydrophobic materials is governed by the Cassie–Baxter or Wenzel models. Moreover, sticky properties, derived from these types of wettings, are required for a wide range of applications involving superhydrophobic materials. As a facile new strategy, a method employing a gaseous fluorine precursor to fabricate core–shell particles, comprising perfectly shaped fluorine shells with adjustable adhesive strength, is described in this paper. Silica was used as the hydrophilic core, while polyvinylidene fluoride (PVDF) was used for the hydrophobic shell coating, forming a raspberry-like shape. In addition, controlling the amount of PVDF coated on the silica surface enabled the water droplets to come into contact with both the PVDF of the shell and the silica of the core, thereby controlling both the superhydrophobicity and the adhesive strength. Thus, the synthesized particles formed a structured coating with controllable stickiness and contact angles of 131–165°. Furthermore, on surfaces with high adhesivity, the water droplets remained stable at tilt angles of 90° and 180° even under a strong centrifugal force, whereas on surfaces with low adhesivity, the water droplets slid off when the substrate was tilted at 4°.